Epigenetic treatment of multiple myeloma mediates tumor intrinsic and extrinsic immunomodulatory effects. (3rd October 2018) - De Beck, Lien; Melhaoui, Sarah; De Veirman, Kim; Menu, Eline; De Bruyne, Elke; Vanderkerken, Karin; Breckpot, Karine; Maes, Ken
ABSTRACT: Immune evasion is an important driver of disease progression in the plasma cell malignancy multiple myeloma. Recent work highlights the potential of epigenetic modulating agents as tool to enhance anti-tumor immunity. The immune modulating effects of the combination of a DNA methyltransferase inhibitor and a histone deacetylase inhibitor in multiple myeloma is insufficiently characterized. Therefore, we used the murine immunocompetent 5T33MM model to investigate hallmarks of immunogenic cell death as well as alterations in the immune cell constitution in the bone marrow of diseased mice in response to the DNA methyltransferase inhibitor decitabine and the histone deacetylase inhibitor quisinostat. Vaccination of mice with 5T33 cells treated with epigenetic compounds delayed tumor development upon a subsequent tumor challenge. In vitro, epigenetic treatment induced ecto-calreticulin and CD47, as well as a type I interferon response. Moreover, treated 5T33vt cells triggered dendritic cell maturation. The combination of decitabine and quisinostat in vivo resulted in combinatory anti-myeloma effects. In vivo, epigenetic treatment increased tumoral ecto-calreticulin and decreased CD47 and PD-L1 expression, increased dendritic cell maturation and reduced CD11b positive cells. Moreover, epigenetic treatment induced a temporal increase in presence of CD8-positive and CD4-positive T cells with naive and memory-like phenotypes based on CD62L and CD44 expression levels, and reduced expression of exhaustion markers PD-1 and TIM3. In conclusion, a combination of a DNA methyltransferase inhibitor and a histone deacetylase inhibitor increased the immunogenicity of myeloma cells and altered the immune cell constitution in the bone marrow of myeloma-bearing mice.